Analisis Kontribusi Usahatani Lada Terhadap Pendapatan Petani di Desa Mowila Kecamatan Mowila Kabupaten Konawe Selatan - Mahardika, Kadek Adi; Bafadal, Azhar; Limi, Muhammad Aswar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aim to knowing pepper farming contribution to farmers' income and knowing the level of efficiency of farming costs pepper. This study is conducted at Mowila village Mowila sub district Konawe Selatan regency. The data used in this study are primary data and secondary data. The population in this study of pepper farmers in the Mowila village totaling 126 people, with the sample of 56 people. The variables were see in this study is cost efficiency, income and contribution farming pepper to the income of farmers. Analysis is theÂ analysis income, contributionÂ and cost efficiency by formula R/C ratio. The results showed that farming pepper contributes to the income of farmersâ€™ amounted to 66.29%, with an average income of Rp 56.601.804/year and cost efficiency farming pepper by 6,63. The abased on the resoults above, the pepper farming in the village Mowila efficient.